Sex-based differences in developing heart failure after ST-segment elevation myocardial infarction - Yuetao Xie; Wenjing Wang; Xuelian Song; Man Gao; Feifei Zhang; Yingxiao Li; Jiaqi Wang; Yi Dang; Xiaoyong Qi (Frontiers in Cardiovascular Medicine, 2026)
Background Previous studies have shown that although advances in primary percutaneous coronary intervention (PCI) and medical therapy have significantly improved the survival of patients with ST-segment elevation myocardial infarction (STEMI), the long-term burden of post-infarction heart failure (HF) remains. Studies on sex differences in the occurrence of HF after STEMI are limited. The aim of this study is to investigate the risk factors and gender differences of HF in STEMI patients after PCI. Methods We conducted a retrospective cohort study, including a total of 1,040 consecutive patients with STEMI. Clinical, laboratory and surgical-related data of the patients were collected. The primary endpoint was the incidence of new-onset HF, and the secondary endpoint was all-cause mortality during the follow-up period. The cumulative event survival rate was estimated using the Kaplan–Meier method. Univariate and multivariate Cox proportional hazards regression analyses were used to determine the independent predictors of HF. Through subgroup and interaction analyses, the consistency of the association between gender and heart failure in different clinical subgroups was evaluated. Results Compared to men, women were significantly older, had a higher prevalence of diabetes, and experienced longer door-to-balloon times. During follow-up, women exhibited a significantly higher crude incidence of HF (25.88% vs . 17.86%, P = 0.007) and all-cause mortality (12.72% vs . 6.53%, P = 0.002). Kaplan–Meier analysis confirmed a higher risk of HF in women (Log-rank P = 0.006). In univariate Cox analysis, female sex was associated with an increased risk of HF. However, after conducting multivariate adjustments, women no longer served as an independent predictor for HF. Significant interactions were observed between sex and diabetes mellitus ( P interaction = 0.010) and Killip class ( P interaction < 0.001). Women with diabetes, a longer time from symptom onset to first medical contact, and a Killip class of II or above have a much higher risk of developing heart failure. Mediation analysis indicated that diabetes mellitus acted as a significant mediator, explaining 21.76% of the total effect of sex on new-onset HF. Conclusion Women have higher HF morbidity and mortality after STEMI, but this difference is mainly driven by their older age and greater burden of comorbidities, not just biological sex.